Old Age Exacerbates White Matter Neuroinflammation and Cognitive Deficits Following Closed-Head Injury, Particularly in Female Mice - Teresa Macheda; Margaret R. Andres; Lydia Sanders; Kelly N. Roberts; Ryan K. Shahidehpour; Josh M. Morganti; Adam D. Bachstetter (Neurotrauma Reports)
The increasing incidence of traumatic brain injury (TBI) among older adults, particularly mild injuries from falls, underscores the need to investigate age-related outcomes and potential sex differences in response to TBI. Although previous research has defined an aging-TBI signature (heightened glial responses and cognitive impairment) in open-skull moderate-to-severe TBI models, it is unknown whether this signature is also present in mild closed-head injuries (CHIs). This study explores the influences of age and sex on recovery in a mouse CHI model induced by an electromagnetic impactor device in 4-month-old and 18-month-old C57BL/6 mice. We assessed the righting reflex, body weight, behavior (radial arm water maze and active avoidance), and inflammation (GFAP, IBA1, CD45) in the neocortex, corpus callosum, and hippocampus. We observed that aged female mice exhibited more severe TBI-induced cognitive deficits. In addition, a more pronounced reactive neuroinflammatory response with age was noted within white matter regions. Conversely, gray matter regions in aged animals either showed no enhanced pathological changes in response to injury or the aged mice displayed hyporesponsive glia and signs of dystrophic glial degeneration that were not evident in their younger counterparts following CHI. These findings suggest that aging influences CHI outcomes, partially reflecting the aging-TBI signature seen in more severe injuries in white matter, while a distinct aging and mild-TBI signature was identified in gray matter. The heightened vulnerability of females to the combined effects of age and mild CHI establishes a foundation for further investigation into the mechanisms underlying the sexually dimorphic response in aging females.